Manipulating Amino Acid Metabolism to Improve Crop Nitrogen Use Efficiency for a Sustainable Agriculture - Dellero, Younès (Frontiers in Plant Science, 2020)
In a context of a growing worldwide food demand coupled to the need to develop a sustainable agriculture, it is crucial to improve crop nitrogen use efficiency (NUE) while reducing field N inputs. Classical genetic approaches based on natural allelic variations existing within crops has led to the discovery of quantitative trait loci controlling NUE under low nitrogen conditions, however the identification of candidate genes from mapping studies is still challenging. Amino acid metabolism is the cornerstone of plant N management, which involves N uptake, assimilation, and remobilization efficiencies and it is finely regulated during acclimation to low N conditions and other abiotic stresses. Over the last two decades, biotechnological engineering of amino acid metabolism has led to promising results for the improvement of crop NUE, and more recently under low N conditions. This review summarizes current work carried out in crops and provides perspectives on the identification of new candidate genes and future strategies for crop improvement.